2018
DOI: 10.1177/0886260518795503
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Concern for Animal Care and Safekeeping: Experiences of Service Providers in Canada

Abstract: The present study examined the experiences of animal welfare and intimate partner violence service providers living in urban, rural, and northern communities in Saskatchewan, Canada. Two online surveys were distributed among animal welfare and intimate partner violence service providers across the province. Quantitative and qualitative information was obtained to further understand how concern for animal care and safekeeping impacts the decision to leave an abusive relationship. The questions asked in the onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…It is evident from the results of the present study that both service providers who work with humans and those who work with animals have a clear understanding of the link. This is in line with previous research conducted in Canada (Crawford & Bohac Clarke, 2012;Stevenson et al, 2018;Wuerch et al, 2020Wuerch et al, , 2021. In both qualitative and quantitative responses, these service providers also indicated that their awareness of the link between IPV, animal abuse, and animal safekeeping had changed or expanded in recent years.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is evident from the results of the present study that both service providers who work with humans and those who work with animals have a clear understanding of the link. This is in line with previous research conducted in Canada (Crawford & Bohac Clarke, 2012;Stevenson et al, 2018;Wuerch et al, 2020Wuerch et al, , 2021. In both qualitative and quantitative responses, these service providers also indicated that their awareness of the link between IPV, animal abuse, and animal safekeeping had changed or expanded in recent years.…”
Section: Discussionsupporting
confidence: 86%
“…Service providers are clear that safety and safekeeping of animals impacts an individual's planning and decision making to leave a relationship when IPV is taking place. Animal welfare and domestic violence service providers indicated that concern for animals was a significant factor in decision making, with some choosing not to leave and some returning to the home to care for pets or livestock-a finding consistent with Wuerch et al (2020Wuerch et al ( , 2021. As with previous research (Wuerch et al, 2020(Wuerch et al, , 2021, professionals indicated that they were aware of people who were experiencing violence but chose not to seek services at a shelter because they could not bring their companion animals with them or because they would not be able to see their pets while they were being fostered or kept at an animal welfare agency.…”
Section: Discussionmentioning
confidence: 75%
“…For this reason, it was important to seek responses from victims/survivors of violence who had not accessed shelter. In addition, extant research primarily focuses on the experiences of victims/survivors who own pets; research on the intersection of IPV and ownership of livestock is limited (Crawford & Bohac Clarke, 2012; Doherty & Hornosty, 2008; Giesbrecht, 2021; Wuerch et al, 2020, 2021).…”
Section: Purposementioning
confidence: 99%
“…When animals have been threatened or harmed, victims fear for the animals' safety if they leave them behind with their partner (Ascione et al, 2007;Barrett et al, 2018Barrett et al, , 2020Collins et al, 2018;Fitzgerald, 2007;Hardesty et al, 2013;Hartman et al, 2018;Stevenson et al, 2018;Wuerch et al, 2020). Research has illustrated that when a victim's companion animal is also harmed by the abusive partner, this impacts decision making-in some cases, women are more likely to delay leaving as they do not want to leave the pet with the abuser; in other cases, harm to animals can solidify a victim's decision to end the relationship and try to escape to safety with their pet (Barrett et al, 2018;Collins et al, 2018;Wuerch et al, 2020Wuerch et al, , 2021.…”
mentioning
confidence: 99%
“…In some cases, victims/survivors of IPV may delay ending relationships because of responsibility for animals, especially when they feel they will not be able to take their animals with them or keep the animals after separation. For others, concern for animals is a catalyst in their decision to end the relationship and escape with their pet (Ascione et al, 2007; Barrett et al, 2018, 2020; Collins et al, 2018; Giesbrecht, 2021a, 2021b; Stevenson et al, 2018; Wuerch et al, 2020, 2021).…”
mentioning
confidence: 99%